Autonomic, metabolic and anthropometric profile of obese patients elective to bariatric surgery (Research, Society and Development, 2020)
Introduction: Obesity is recognized as one of the biggest public health problems in the world and is associated with chronic diseases such as diabetes mellitus, dyslipidemia, and some types of cancer, in addition to sympathetic hyperactivity, which can be an independent risk factor for mortality. Objective: To describe the autonomic, metabolic, and anthropometric profiles of obese patients elective to bariatric surgery. Methods: Cross-sectional study where the autonomic (SDNN, RMSSD, LF, HF, and LF / HF), metabolic (total cholesterol, HDL cholesterol, triglycerides, glucose, insulin, and HOMA - IR), and anthropometric (body mass index) profiles were analyzed, waist circumference, hip circumference, and relative fat) of patients in the preoperative period of bariatric surgery, aged ≥ 21 years, from the Center for Treatment and Obesity Surgery (NTCO) in the city of Salvador-Bahia. Results: The mean age and BMI were 38.1 years and 40.8 kg / m², respectively. The mean abdominal circumference and relative fat were 119 cm and 48.9%, respectively. Regarding the lipid profile, high values of total cholesterol (191 mg / dL) and triglycerides (159.1 mg / dL) were found. In the glycidic profile, the median fasting glucose dosage was 95 mg / dL; insulin: 21.1 mIU / L; HOMA: 5.2. Regarding the autonomic profile, changes were found in the values, in the time domains, with a predominance of SDNN values over RMSSD, and in frequency, a predominance of LH values over HF. Conclusion: Obesity was related to the alteration of the metabolic and autonomic profile of this sample.